Faktor-Faktor yang Mempengaruhi Tingkat Underpricing Perusahaan Manufaktur yang Melakukan Initial Public Offering yang Terdaftar di BEI Periode 2011-2014 - Kurniasari, Yunita; , Dr. Fatchan Achyani, S.E,M.Si (2016)
The aim of this research is to know the influence of the underpricing manufacturing companies in Indonesia Stock Exchange for the period 2011-2014. The population of this research is all of the manufacturing companies registered at Indonesian Stock Exchange during 2011 to 2014. Sampling was done by purposive sampling method and the number of the samples is 92 companies. The data of this research is secondary data. Analysis tool used multiple linear regression. The finding of this research shows that the auditor's reputation, return on equity and the percentage of stock quotes significantly influence underpricing. While the underwriter's reputation and fractional holding had no significant influence to underpricing